L'incontournable usage du cas et de l'exemple dans l'enseignement universitaire - Alice Delserieys; Perrine Martin (Nantes Université, 2016)
The evolution of teaching practices in higher education is at the heart of many debates to face challenges such as low student motivation or the growing heterogeneity amongst student population. In this context, the choice was made to question the use of examples in higher education. It is a frequent practice, shared by lecturer from many areas, but rarely studied by research in education at university level. We first present theoretical considerations in order to propose a definition of what an example in higher education can be. We then consider the questions raised by such practices in the relation between lecturer and students and the effectiveness in terms of student learning. The researches presented in this issue question the didactical choices of lecturer at university when using examples in their courses. It is a based on the opinion of lecturers from different subjects: physics, chemistry, mathematics, history, geography and urbanism. This interest in university lecturers' practices and their multiple uses of examples in class then raises the question of the effectiveness in relation to student engagement and learning.